Influence of cut, packaging and storage temperature on physicochemical aspects of minimally processed Carica papaya cv. ‘Formosa’ - Lima, Paula Cristina Carvalho; Souza, Bianca Sarzi; Fyfe, Selina (Revista de Investigación Agraria y Ambiental, 2018)
This study aims to verify the influence of cut, package and storage temperature on the physicochemical aspects of minimally processed ‘Formosa’ papaya. Fruits were selected, washed and sanitized, then stored for 12 h at 10 ºC. At 12 ºC, they were peeled and cut longitudinally in half, the seeds and tips were removed, then the fruit was cut into slices in the transverse direction (1.5-2-cm thick) or cut into 4 parts. Cut pieces were rinsed, drained and packed either into polyethylene terephthalate (PET) containers or on Styrofoam trays wrapped in polyvinyl chloride (PVC) film and stored at 4 or 8 °C. During storage, they were evaluated for soluble solids, titratable acidity, vitamin C, color (lightness, hue angle and chroma), texture, weight loss and appearance. Physicochemical results showed the products maintained adequate quality for consumption and commercialization for up to nine days. The fruit stored at 4 ºC maintained better texture and color, had lower weight loss and higher levels of vitamin C than those stored at 8 ºC. The PET packaging minimized weight loss and the transverse direction cut type promoted less damage to the tissues, maintaining the quality and characteristics of the fresh fruit.